An antihypertensive move: technology to mediate teaching practices with health students about medications - Jéssica Gomes da Silva; Laidiane Dantas Soares Pena; Amiraldo Dias Gama; Érika Tatiane de Almeida Fernandes Rodrigues; Elizabeth Teixeira; Francineide Pereira da Silva Pena; Diego Quaresma Ferreira (Revista Gaúcha de Enfermagem)
ABSTRACT Objective: To verify evidence of validity of the board game “An antihypertensive move” produced to mediate teaching practices with students on health courses about diuretic and antihypertensive medications. Method: this is a methodological and development study in compliance with the SQUIRE-EDU guidelines. 20 experts participated. In data collection, the Health Educational Content Validation Instrument (IVCES) and the Health Educational Technology Appearance Validation Instrument (IVATES) were applied. For the analysis, the Content Validation Index (CVI), the Appearance Validation Index (IVA), descriptive statistics and the Binomial Test were used. Results: in content validation, a CVI of 0.92 was obtained (first and only round); in appearance validation VAT of 0.83 (in the first round) and 1.00 (in the second round). Conclusion: the game is adequate in terms of content and appearance and is a valid technological device to mediate teaching practices about medicines.